Carbohydrate and caffeine mouth rinses do not affect maximum strength and muscular endurance performance - Clarke, N. D.; Kornilios, E.; Richardson, D. L. (The Journal of Strength and Conditioning Research, 2015)
Oral carbohydrate (CHO) rinsing has beneficial effects on endurance performance and caffeine (CAF) mouth rinsing either independently or in conjunction with CHO may enhance sprinting performance. However, the effects of CHO and CAF mouth rinses on resistance exercise have not been examined previously. The purpose of this study was to investigate the effects of CHO and CAF rinsing on maximum strength and muscular endurance performance. Fifteen recreationally resistance-trained males completed an exercise protocol, which involved a 1 repetition maximum (RM) bench press followed by 60% of their 1RM to failure in a double-blind, randomized, counterbalanced crossover design. Before exercise, 25 ml of a 6% (15 g; 0.20 ± 0.02 g/kg) CHO, 1.2% (300 mg; 3.9 ± 0.3 mg/kg) CAF, carbohydrate with caffeine (C + C) solutions, or water (placebo; PLA) were rinsed for 10 seconds. During the remaining session, no solution was rinsed (control; CON). All solutions were flavored with (200 mg) sucralose. Felt arousal was recorded pre- and postrinse, and rating of perceived exertion (RPE) was recorded immediately after the repetitions to failure. There were no significant differences in 1RM (p = 0.808; np^2 = 0.02), the number of repetitions performed (p = 0.682; np^2 = 0.03), or the total exercise volume (p = 0.482; np^2 = 0.03) between conditions. Rating of perceived exertion was similar for all trials (p = 0.330; np^2 = 0.08), whereas Felt arousal increased as a consequence of rinsing (p = 0.001; np^2 = 0.58), but was not different between trials (p = 0.335; np^2= 0.08). These results suggest that rinsing with a CHO and CAF solution either independently or combined has no significant effect on maximum strength or muscular endurance performance.